Development of a Problem Based Learning Media to Build Mathematical Communication Capabilities Students of Class VIII Junior High School - Hany Zahira; Zulkarnain Zulkarnain; Putri Yuanita (Universitas Riau, 2020)
This research was motivated by the difficulties of teachers in implementing the 2013 curriculum, especially in the preparation of learning tools. This research was aimed to develop a valid, practical and effective learning tool for VIII grade junior high school students. This type of research was Research and Development with a 4-D model. Data collection instruments in this study were validation sheets, practicality sheets and tests of mathematical communication skills. Data were analyzed using validation criteria, practicality and effectiveness tests. The results obtained from the device validation show that the RPP is valid and the LKPD is quite valid. The practicality test results of small groups and large groups obtained very practical criteria. The effectiveness test can be seen from the percentage of student KKM achievement that is equal to 92% meets the effective criteria and the average difference test (t test) is obtained that tcount> ttable, which is 16.976> 1.677 and the significance value is <0.05. These results indicate that the developed learning tools are effective in improving students mathematical communication skills.